Kinerja profitabilitas Bank Mega Syariah berdasarkan rasio ROA tahun 2020–2024 - Sabil, Bahri -; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study analyzes the profitability performance of Bank Mega Syariah as measured by Return on Assets (ROA) during the 2020-2024 period. A descriptive quantitative approach was employed using secondary data from the bank’s annual financial reports. The findings reveal fluctuations in ROA performance with a generally declining trend. ROA stood at 2.68% (2020), increased to 3.02% (2021), then gradually declined to 2.86% (2022), 2.66% (2023), and reached its lowest point of 1.95% (2024). This decline was influenced by internal factors including decreased net profit, pressure on income margins, and suboptimal operational efficiency. External factors encompassed post-pandemic economic conditions, regulatory changes, and increasingly intense competition in the Islamic banking industry. The study concludes that Bank Mega Syariah needs to optimize asset management and diversify revenue sources to improve its profitability performance in the future.